The influence of riparian vegetation on water quality in a mixed land use river basin. (15th February 2019) - Chua, Evan M.; Wilson, Scott P.; Vink, Sue; Flint, Nicole
Abstract: Worldwide, agricultural activities are associated with environmental impacts including riparian degradation and increased waterway pollution. The Fitzroy Basin of Central Queensland lies within the Brigalow Belt Bioregion, which is currently experiencing the highest rates of tree clearing in Australia driven by grazing activities, and this is likely to increase riparian degradation. Local riparian condition, however, has not been consistently monitored within the Fitzroy Basin, and its relationship with water quality has not been well established. This study assessed riparian condition of waterways in the Fitzroy Basin using two established scoring methods (the Rapid Appraisal of Riparian Condition and the Australian Rivers Assessment System Habitat Assessment) and statistically investigated the relationship between stream water quality and local riparian condition. Twelve sites in six waterways were sampled four times over two years, during ambient (nonflood) conditions. Upstream creeks with poorer riparian condition had elevated dissolved organic carbon (DOC), dissolved manganese, sulfate, and total nitrogen (TN) concentrations. High concentrations of these water quality variables were associated with poor local riparian scores in principal components analysis. Dissolved manganese and sulfate were included in the multiple regression model for riparian scores ( r values: 0.83 to 0.86; p  < 0.001), and DOC and TN were very significantly negatively correlated with riparian scores ( r values: −0.55 to −0.69; p  < 0.001). Overall, the results suggest that protecting riparian vegetation in the Fitzroy Basin and restoring degraded riparian zones could aid in improving water quality in waterways within this region.